PEMANFAATAN SIMBIOSIS MIKROALGA Chlorella sp DAN AGROBOST UNTUK MENURUNKAN KADAR POLUTAN LIMBAH CAIR SAGU - FADLA B. SYARIF; FAJAR RESTUHADI; YELMIRA ZALFIATRI (Universitas Riau, 2019)
The purpose of this research was to get the best treatment addition of Agrobost microorganisms as a reducingagent of pollutant from sago liquid waste with the addition of microalgae Chlorella sp. This research used aCompletely Randomized Design (CRD) with 5 treatments and 3 replications. The treatments in this additionwas microalgae Chlorella sp. as much 800 ml/L (6.292.000 cell/ml) of sago liquid waste with some variousconcentrations of Agrobost (0% v/v, 1% v/v, 2% v/v, 3% v/v, dan 4% v/v). The data obtained were analyzedstatistically using ANOVA and DNMRT at 5 % level. The result showed that the addition of Agrobostmicroorganisms significantly affected COD, BOD, TSS, nitrate, phosphate, DO and pH of sago liquid waste.The chosen treatment from the result of this research was the P2 treatment showing the best level of reductionof COD 88,65%, BOD of 91,41%, TSS of 63,96% and the increase in the pH of 92,50%, DO of 56,51%.